Manifestasi Nilai Kemanusiaan dalam Cerpen Kontemporer dan Relevansinya Sebagai Materi - Eny Junyanti; Nazla Maharani Umaya (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research examines the manifestation of humanistic values in six selected short stories from Kompas in 2021-2022 as an alternative literary teaching material. The phenomenon of declining understanding of humanitarian values among students and the importance of instilling these values through literary works serve as the background for this study. The goal is to identify and analyze the representation of humanism in contemporary Indonesian literature. The research method uses a descriptive qualitative approach with content analysis techniques. The analysis results show that the six short stories studied are rich in humanistic values such as openness, responsibility, solidarity, justice, self-sacrifice, care, and mutual assistance. The structure of a short story, including characters and setting, plays an important role in conveying those values.